REDUCTION OF OUTLIERS IMPACT IN LEAD RESERVES DATA USING ROBUST KRIGING - DEVILA (10112068), SINDY
Mining activities, especially metal, usually encounter extreme values (outliers). Such problem may cause the data no longer normally distributed. Consequently, spacial estimation process using ordinary kriging gives inaccurate result. To overcome this issue, a modification in kriging predictor equation is needed. The robust kriging procedure can be used to estimate lead reserves which have been modeled using Matheron, Cressie-Hawkins, and Dowd semivariogram. It will be shown that RoK along side with Doed semivariogram give the best, unbiased, and more accurate prediction.